Inventarisasi Arthropoda Di Bendungan Pengga Kabupaten Lombok Tengah - Siti Nurhaida; Muhsinul Ihsan; Firman Rahman (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2024)
One of the potential areas for Arthropod inventory research is the Pengga Dam in Central Lombok. Vegetation type affects the number of arthropods found in the habitat. Vegetation type affects the thick or humid conditions and litter diversity, which can directly affect the diversity of Arthropods that inhabit it. The purpose of this study was to determine what types of Arthropods are in the Pengga Dam in Central Lombok. Sampling was carried out using pitfall traps, using insect nets and documentation. The results of the study showed that the types of Arthropods found in the Pengga Dam, Central Lombok were 20 species, namely: Telebasis digiticollis, Ischnura senegelensis, Ischnura elegans, Acisoma panorpoides, Potamorcha congener, Neorothemis terminate, Orthetrum sabina, Castalius rosimon, Eurema sari, Neptis hylas, Junonia hedonia, Zizina otis, Chalybion californicum, Schelipron caemenrarium, Oecophylla smaragdina, Anochetus incultus, Technomyrmex grandis, Dytiscus marginalis, Arctosa cinerea, and Pardosa amentata.